2009
DOI: 10.1002/bmc.1322
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity enhancement and matrix effect evaluation during summation of multiple transition pairs—case studies of clopidogrel and ramiprilat

Abstract: Sensitivity enhancement via summation of multiple MRM transition pairs is gaining popularity in tandem mass spectrometric assays. Numerous validation experiments describing the assays for two model substrates, clopidogrel and ramiprilat, were performed. The quantitation of clopidogrel was achieved by the summation of transition pairs m/z 322.2 to m/z 212.0 and m/z 322.2 to m/z 184.0, while that of ramiprilat was achieved by the summation of transition pairs m/z 389.2 to m/z 206.1 and m/z 389.2 to m/z156.1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In-source ions ( m / z 133.1, 177.1, 353.1, 397.2, 441.2) with relatively high abundance were subjected to further dissociation in the positive ESI-MRM mode and the summation of five transitions (see the Experimental Section) were employed to quantify both 40k PEG and ATI-1072 (LLOQ 0.05 μg/mL for both analytes). The approach of using the summation of multiple MRM transitions to increase the sensitivity is now increasingly considered in the LC-MS/MS analysis . In the current study, using the total signals from 5 MRM transitions instead of 1 transition increased the assay sensitivity by at least 3-fold.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In-source ions ( m / z 133.1, 177.1, 353.1, 397.2, 441.2) with relatively high abundance were subjected to further dissociation in the positive ESI-MRM mode and the summation of five transitions (see the Experimental Section) were employed to quantify both 40k PEG and ATI-1072 (LLOQ 0.05 μg/mL for both analytes). The approach of using the summation of multiple MRM transitions to increase the sensitivity is now increasingly considered in the LC-MS/MS analysis . In the current study, using the total signals from 5 MRM transitions instead of 1 transition increased the assay sensitivity by at least 3-fold.…”
Section: Resultsmentioning
confidence: 66%
“…For the quantitative analysis of 40k PEG and ATI-1072, the following MRM (multiple reaction monitoring) transitions of PEG-specific ions were selected: m / z 133.1 → m / z 89.1, m / z 177.1 → m / z 89.1, m / z 353.2 → m / z 89.1, m / z 397.2 → m / z 133.1, and m / z 441.2 → m / z 133.1. To improve assay sensitivity, the summation of the signals from five transitions was used for standard curve and sample analysis . The standard curves with the concentrations ranged from 0.05 to 20 μg/mL were fitted to a quadratic regression model using weighting factors 1/ x . , Concentrations of 40k PEG and ATI-1072 were calculated using the Analyst software (Version 1.6, AB Sciex) based on their MRM responses and standard curves.…”
Section: Experimental Detailsmentioning
confidence: 99%
“…However, a single SRM transition pair appeared to be adequate for fimasartan to achieve appropriate sensitivity and for IS alprazolam. The summations of SRM transition pairs have been previously used in a beneficial manner to improve the sensitivity of the assays without any compromise in the assay performance (Manjunath Swamy, Kamath, Radha Shekar, Srinivas, & Kristjansson, 2010; Srinivas, 2009b). Before execution of full validation, a long batch ( n = 30/concentration) including LLOQ (5 ng/mL), LQC (15 ng/mL), MQC (6000 ng/mL) and HQC (7500 ng/mL) was run to ensure assay reproducibility.…”
Section: Resultsmentioning
confidence: 99%
“…Another aspect of the study was with respect to summation of responses from two MRM transition pairs to improve the sensitivity of the quantitation (Ferreirós et al, ). Previously, it has been demonstrated that for drugs such as clopidogrel and ramiprilat, sensitivity for analysis can be increased with summation of stable MRM transition pairs; however, it is equally important to ensure that such sensitivity enhancement is devoid of the matrix effect (Manjunath Swamy, Kamath, Radha Shekar, Srinivas, & Kristjansson, ; Srinivas, ).…”
Section: Discussionmentioning
confidence: 99%